Pengembangan E-Modul Berbasis Microlearning Pada Mata Kuliah Pembelajaran Bahasa Sunda Di Sd - Evi Rahmawati; Rahmat Sutedi (Universitas Muhammadiyah Surabaya, 2026)
This study aimed to develop a microlearning-based e-module for the Elementary School Sundanese Language Teaching course. The research employed the Design and Development (D&D) method using the PPE (Planning, Production, and Evaluation) model. Participants included a content expert, a language expert, a media expert, and third-semester students of the Primary School Teacher Education Program at Universitas Pendidikan Indonesia. Data were collected through interviews and questionnaires. Validation results indicated that the e-module was highly feasible in terms of content, language, and media aspects. The average validation scores were 90% from the content expert, 88% from the language expert, and 86% from the media expert. Student responses yielded an average score of 92%, also categorized as highly feasible. The developed e-module comprises five learning resources: text modules, presentation slides, infographics, explainer videos, and podcasts. These findings indicate that the microlearning-based e-module is suitable for use as teaching material in the course.